Performance analysis of coconut enterprises facilitated through agribusiness incubators - Ashwini, T.; Bonny, Binoo P.; Lokesh, S. (Journal of Plantation Crops, 2020)
Agribusiness incubators (ABI) catalyze entrepreneurship development by facilitating technology and institutionalized services. The study addresses the performance analysis of enterprises promoted through coconut sector ABIs working in Kerala. Primary and secondary data collected from 30 randomly selected ABI graduated entrepreneurs in business were used to characterize the enterprises. The results indicated that 56 per cent of enterprises joined ABIs at the nascent stage and were able to receive government funding under different subsidy schemes. Majority of enterprises (72%) shared features of micro-enterprises in terms of the number of persons employed (01-10) and annual turnover less than ` 25 lakh. Most of the micro-enterprises (66%) functioned as sole proprietary firms, whereas small enterprises were registered as limited company/partnership firms (20%). Virgin coconut oil (VCO) was the major product in 40 per cent of enterprises followed by coconut chips (20%), coconut chocolates (10%), desiccated coconut (07), neera and tender coconut water-based drinks (07%). Performances of two purposively selected enterprises producing VCO and coconut chips were undertaken using break-even analysis. Production and sales of both VCO and coconut chips were more than the calculated BEP values of 1000 litres and 500 kg respectively. This indicated that both enterprises operated at profitable levels. The findings suggest that the entrepreneurs who completed the business incubation program had greater success in their business irrespective of the business size. This can be attributed to their greater access to technologies and entrepreneurship development programmes under the ABI.